Decoding the restructuring expert: role, skills, and challenges - Arroyo Egido, Inocencio; Gelashvili, Vera; Segovia Vargas, María Jesús; Camacho-Miñano, María del Mar (Journal of Management and Business Education, 2025)
In this paper, the new figure of the Restructuring Expert that has emerged with Directive (EU) 2019/1023 will be analyzed, but, above all, with the transposition in Spain carried out with Law 16/2022 of September 5. Since the figure is not reflected in the European and US environment, for the development of the article, the concepts are first framed through a documentary review, both of what is understood as ordinary business restructuring, as well as the historical development of pre-bankruptcy figures, and the treatment in the current regulatory framework. The figures found in the international framework are mentioned and the analysis of business restructuring is included both for business management and for the early management of the business crisis. With this analysis and, in view of the performances that the norm requires of the Restructuring Expert, the skills required in the exercise of the new profession will be extracted. The study aims to understand in detail the activities that the new restructuring expert has to carry out in order to establish the skills and abilities necessary to carry out his work with guarantees of success.